Plankton Community Structure as a Bioindicator of Water Quality in the Way Sekampung River- the Segment of Rulung Helok - Tugiyono, Tugiyono; Ayuni, Ubaid Jan; Priyambodo, Priyambodo; Susanto, Gregorius Nugroho (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
Planktons are microorganisms that live in aquatic habitats. Plankton is used as a quality bioindicator of a water body. Way Sekampung flows to several areas in Lampung Province. The existence of activities around the watershed such as settlements, agriculture, and industrial waste disposal is thought to affect the water quality of the Way Sekampung River. The purpose of this study was to determine the water quality of Way Sekampung River based on plankton community structure consisting of abundance index, diversity index, uniformity index, and dominance index. Water sample data were analyzed using chemical parameters namely pH, BOD, DO, Phosphate, Nitrate, and physical parameters namely temperature and Total Suspended Solid (TSS) which are used to determine the status of water quality standards. This research was conducted at the beginning of the dry season (April) and the beginning of the rainy season (October). Sampling used a survey method based on the Way Sekampung River segment. Sampling points were carried out before and after the Argoguruh Dam. The results showed that the water quality of Way Sekampung River at the beginning of the dry season (April) and the beginning of the rainy season (October) were moderately polluted based on the analysis of plankton community structure such as abundance index, diversity, uniformity, and dominance.